The Role of Political Skill in Bigg Boss: Strategies for Survival and Behavioral Competencies in Reality Show - Jain, Vikas; Tiwari, Shivani (Information & Media, 2024)
This study investigates how political skill turns into success on Bigg Boss, an Indian reality TV show. Political skill, involving adaptability and influence, is known to be valuable in organizations, but its reach beyond business is unexplored. This study analyzes Bigg Boss Season 14 to address this gap. A purposive and convenience sampling method was utilized. Housemates’ behaviors were analyzed through content analysis with a summative approach, identifying five key aspects of political skill: influencing, sincerity, deceitfulness, social astuteness, and networking. Housemate statements were translated and analyzed to identify recurring themes and patterns. Correlations between these behaviors and success in the game were examined. Results showed a link between all five behaviors and success, suggesting housemates who exhibited them more often lasted longer. The winner displayed the most social astuteness, followed by sincerity, networking, influencing, and lastly, deceitfulness. These findings highlight that political skill, characterized by a strategic combination of social behaviors, is key to winning Bigg Boss. The study offers a broader understanding of political skill by demonstrating its applicability beyond business and emphasizing the importance of using these behaviors skillfully and adaptively. It also suggests connections to other academic fields, opening doors for future research.